A new species of Halaphanolaimus (Nematoda: Leptolaimidae) from the southern Black Sea (Turkey) with a modified key for species identification - Ürkmez, Derya; Brennan, Michael L. (Zootaxa, 2013)
Halaphanolaimus sergeevae n. sp. is described and illustrated from the Sinop coasts (southern Black Sea, Turkey). The new species morphologically resembles H. pellucidus Southern, 1914, but differs from it by having a higher number of tubular supplements (12–14 vs 6–7), longer spicules (68–70 µm vs 47–52 µm), smaller tail/spicule ratio (1.6 vs 2.7), smaller body size (926–1273 vs 1500 μm), and smaller De Man indices of a, b and c’. An updated identification key to the species of Halaphanolaimus is proposed.